A STUDY OF THE PROGRESS OF MAHARASHTRA STATE CO-OPERATIVE BANK - Pande, Pooja D.; Gulhane, Rekha M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
State Co-operative banks functions as the apex bank of all the co- operative banks in the state. Being the bank of all District Central Co-operative banks. State Co-operative Bank accepts deposits from its members among District central co-operative banks, individual members as well as co-operative societies. The bank also accepts deposits from Zilla Parishad, educational institutions, municipal council, etc. The State co-operative banks accept deposits on a large scale and fulfil the requirement of working capital of District Central co-operative banks.